DESIGNING TEACHER PROFESSIONAL DEVELOPMENT FOR MATHEMATICS TEACHING WITH VARIATION THEORY - Rooselyna Ekawati; Fou-Lai Lin (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2014)
In this study, we aimed at demonstrating the power of Variation Theory in exploring the local situation of Indonesian teachers and Teacher Professional Development program. The projection of Variation theory regarding the enterprise of teaching results on the need of sensitivity of students and exemplary teaching strategy that differ with teachers teaching style. Besides, It requires more opportunities for teachers to understand the critical feature of object of learning. By sequence of activity that elaborating variation theory and regards the local situation might imply the improvement of students learning.Keywords: Variation Theory, Teacher Professional Development, Indonesia DOI: http://dx.doi.org/10.22342/jme.5.2.1497.127-137